Cutting care clusters: the creation of an inverse pharmacy care law? An area-level analysis exploring the clustering of community pharmacies in England. Issue 7 (1st August 2018) - Todd, Adam; Thomson, Katie; Kasim, Adetayo; Bambra, Clare
Abstract : Objectives: To (1) explore the clustering of community pharmacies in England and (2) determine the relationship between community pharmacy clustering, urbanity and deprivation. Design: An area-level analysis spatial study. Setting: England. Primary and secondary outcome measures: Community pharmacy clustering determined as a community pharmacy located within 10 min walking distance to another community pharmacy. Participants: Addresses and postal codes of each community pharmacy in England were used in the analysis. Each pharmacy postal code was assigned to a lower layer super output area, which was then matched to urbanity (urban, town and fringe or village, hamlet and isolated dwellings) and deprivation decile (using the Index of Multiple Deprivation score). Results: 75% of community pharmacies in England were located in a 'cluster' (within 10 min walking distance of another pharmacy): 19% of community pharmacies were in a cluster of two, while 56% of community pharmacies were in clusters of three or more. There was a linear relationship between community pharmacy clustering and social deprivation—with clustering more prevalent in areas of higher deprivation: for community pharmacies located in areas of lowest deprivation (decile 1), there was a significantly lower risk of clustering compared with community pharmacies located in areas of highest deprivation (relative risk 0.12 (95% CI 0.10 to 0.16)). Conclusions: Clustering of community pharmacies in England is common, although there is a positive trend between community pharmacy clustering and social deprivation, whereby clustering is more significant in areas of high deprivation. Arrangements for future community pharmacy funding should not solely focus on distance from one pharmacy to another as means of determining funding allocation, as this could penalise community pharmacies in our most deprived communities, and potentially have a negative effect on other healthcare providers, such as general practitioner and accident and emergency services.